Crystallization and biochemical characterization of an archaeal lectin from Methanococcus voltae A3. Issue 5 (1st May 2017) - Sivaji, N.; Abhinav, K. V.; Vijayan, M.
Abstract : An archaeal lectin from Methanococcus voltae A3 has been cloned, expressed, purified and crystallized, and the crystals have been characterized using X‐ray diffraction. Abstract : A lectin from Methanococcus voltae A3 has been cloned, expressed, purified and characterized. The lectin appears to be specific for complex sugars. The protein crystallized in a tetragonal space group, with around 16 subunits in the asymmetric unit. Sequence comparisons indicate the lectin to have a β‐prism I fold, with poor homology to lectins of known three‐dimensional structure.